2021
DOI: 10.12688/f1000research.51333.2
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and compliance with Covid-19 infection prevention and control measures among health workers in regional referral hospitals in northern Uganda: a cross-sectional online survey

Abstract: Background: Infection prevention and control (IPC) has increasingly been underscored as a key tool for limiting the transmission of coronavirus disease 2019 (Covid-19) and safeguarding health workers from infections during their work. Knowledge and compliance with IPC measures is therefore essential in protecting health workers. However, this has not been established among health workers in northern Uganda in light of the Covid-19 pandemic. The objective of this study was to determine the knowledge and complia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
2
4
1
Order By: Relevance
“…In comparison to the more than 60% of respondents who had adequate knowledge, adherence to the safety protocols was woefully low. This finding contradicts the findings of previous studies, which found that having adequate knowledge resulted in higher adherence [ 51 , 52 ]. However, other studies suggested that adequate knowledge does not always result in higher adherence [ 53 ].…”
Section: Discussioncontrasting
confidence: 99%
“…In comparison to the more than 60% of respondents who had adequate knowledge, adherence to the safety protocols was woefully low. This finding contradicts the findings of previous studies, which found that having adequate knowledge resulted in higher adherence [ 51 , 52 ]. However, other studies suggested that adequate knowledge does not always result in higher adherence [ 53 ].…”
Section: Discussioncontrasting
confidence: 99%
“…The rate of reporting good preventive practices was 1.9 times higher in females than in males. Similar ratios were reported by three other studies in Ethiopia ( 42 , 51 , 52 ) and by studies in Bangladesh ( 53 ), Uganda ( 54 ), Syria ( 37 ), Jordan ( 55 ), Iran ( 56 ), Beijing ( 57 ), Bangladesh ( 29 ), and in Saudi Arabia ( 58 ).…”
Section: Discussionsupporting
confidence: 89%
“…Students who had received IPC training were 1.91 times more likely to mention good preventive practices than those without IPC training, corroborating a study on health workers in Uganda ( 54 ) and frontline health workers in Nepal ( 61 ).…”
Section: Discussionsupporting
confidence: 72%
“…Whilst IPC measures were not explicitly changed for COVID-19 wards in either country, guidance in both emphasised the adherence to and continued use of existing IPC guidance. IPC changes and compliance are difficult to quantify using guidelines alone and it was not possible to establish a clear causal relationship in this study [60,61]. Systematically measuring the use of PPE, hand hygiene and ward cleaning routines and its effect on AMR and HAI transmission merits further research [62,63].…”
Section: Discussionmentioning
confidence: 99%